Evaluation of different nitrogen management protocols for yield, nutrient uptake and economics under various establishment methods in rice (Oryza sativa)-wheat (Triticum aestivum) systemunder Trans-Gangetic Plains of India - G D, SANKETH; SHEKHAWAT, KAPILA; RATHORE, S S; SINGH, RAJIV KUMAR; BABU, SUBHASH; KUMAR, VIPIN; SONAD, PRAKASH (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2022–23 and 2023–24 at ICAR-Indian Agricultural Research Institute, New Delhi to investigate the effects of precision nitrogen (N) management, including nano-urea under various crop establishment approaches on productivity and N uptake in rice (Oryza sativa L.) and wheat (Triticum aestivum L.). The experiment was laid out in split-plot design (SPD) with three replications. The treatments involved 3 main-plots with establishment M1, Vattar direct-seeded rice (VDSR) followed by conventional till-wheat (CTW) + rice residue at 3 t/ha; M2, Dry direct seeded rice (DDSR) followed by zero till-wheat (ZTW) + rice residue at 3 t/ha; and M3, Puddled transplanted rice (PTR) followed by CTW without residue and five sub-plots with variable N management practices [N0, No N; N1, Modified N application (No Basal + 3 Split N (33% each @15–20; 40–45 and 60–65 DAT/DAS); N2, LCC- guided N application at LCC (≤3) for rice @30 kg/ha from 15–65 DAS and in wheat N use at LCC (≤4) @40 kg/ha from 20–65 DAS; N3, 25% N as Basal + 25% N at 30 DAS/DAT + 2 Nano-urea sprays at maximum tillering (MT) and panicle initiation (PI) in rice and in wheat 25% N as Basal + 25% N at 30 DAS + 2 Nano-urea sprays at MT and peak flowering (PF); N4, 25% N as Basal + 25% N at 25 DAS/DAT + 25% N at 40 DAS/DAT + 2 Nano-urea sprays @ MT and PI in rice and in wheat 25% N as Basal + 25% N at 25 DAS/DAT + 25% N at 45 DAS/DAT + 2 Nano-urea sprays @MT and PF].The study showed that leaf colour chart (LCC)-guided balanced N application led to higher grain yield and N uptake in all establishment techniques for both rice and wheat. It was followed by 3 split applications of N (farmer’s practice), which remained on par with 75% N in splits + 2 nano-urea sprays. The highest rice grain yield and N uptake were recorded under PTR during both years. In the first year, rice grain yield and N uptake in PTR were 4.5 t/ha and 109.3 kg/ha, respectively which remained statistically on par with VDSR (4.3 t/ha and 103.1 kg/ha, respectively). It was followed by DDSR with grain yield and N uptake of 4.05 t/ha and 90.7 kg/ha, respectively. The rice grain yield obtained under PTR was 4.6 t/ha, which was 5.6% and 11.1% higher than VDSR and DDSR, respectively. However, this increase was 8.1% and 17.7% for N uptake in TPR over VDSR and DDSR. In the first year of the experiment, the highest wheat grain yield and N uptake were recorded with ZTW + rice residue @3 t/ha (4.5 t/ha and 131.9 kg/ha), respectively which was found on par with CTW + rice residue @3 t/ha (4.4 t/ha and 125.4 kg/ha). It was followed by CTW without residue (4.2 t/ha and 115.3 kg/ha, respectively) and a similar trend was observed in the second year also. A respective increase of 8.1% and 5.3% in wheat grain yield and 13.1% and 9.1% in N uptake was recorded under ZTW + rice residue and CTW + rice residue over CTW without residue.